2021
DOI: 10.3390/brainsci11050564
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between 17β-Estradiol and TGF-β Signaling Modulates Glioblastoma Progression

Abstract: Epithelial–mesenchymal transition (EMT) is an essential mechanism contributing to glioblastoma multiforme (GBM) progression, the most common and malignant brain tumor. EMT is induced by signaling pathways that crosstalk and regulate an intricate regulatory network of transcription factors. It has been shown that downstream components of 17β-estradiol (E2) and transforming growth factor β (TGF-β) signaling pathways crosstalk in estrogen-sensitive tumors. However, little is known about the interaction between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
(98 reference statements)
1
12
0
Order By: Relevance
“…Previous studies showed that E2 induces cell proliferation and the expression of genes involved in mitochondrial metabolism in glioblastomas [ 29 ]. The treatment of glioblastoma cells with E2 resulted in decreased expression of the TGF-β intracellular signaling proteins R-Smads [ 30 ]. In another study, TGF-β1 induced activation of the Wnt/β-catenin pathway during the EMT processes.…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%
“…Previous studies showed that E2 induces cell proliferation and the expression of genes involved in mitochondrial metabolism in glioblastomas [ 29 ]. The treatment of glioblastoma cells with E2 resulted in decreased expression of the TGF-β intracellular signaling proteins R-Smads [ 30 ]. In another study, TGF-β1 induced activation of the Wnt/β-catenin pathway during the EMT processes.…”
Section: Drivers Of Emt In Glioblastomamentioning
confidence: 99%
“…However, we now know that many of these reported ERα-negative cell lines actually do express low/extremely low levels of ERα ( e.g. MDA-MB-468/453, 65,66 SK-BR-3, 67 U87MG, 68,69 OVCAR-3 (ref. 70 and 71)).…”
Section: Anticancer Activity Of 33-bis(4-hydroxy Phenyl)indoline-2-onesmentioning
confidence: 99%
“…SK-BR-3, 67 U87MG,68,69 OVCAR-3 (ref.70 and 71)). When looking at the in vivo tumor models reported in the work, TOP216 shows efficacy in models that all express ERα (MCF-7,72 PC-3,73,74 MDA-MB-468,65,66 MiaPaca,75 and A2780 (ref.71 and 76)).…”
mentioning
confidence: 99%
“…Understanding characteristic features of glioma cells emerges as an important path to reveal the heterogeneity of GBM microenvironment to provide therapeutic approaches that successfully target the right subsets of glioma cells in GBM and eventually maximize efficacy and minimize the side effects of the applied therapy [5][6][7][8]. Glioma cells display striking cellular heterogeneity by changing their morphology [9][10][11], nuclear volume [12][13][14], cell-cell adhesion [15,16], cellular interaction [17], cytoskeleton organization [18][19][20][21], and by performing epithelial-to-mesenchymal transitions [22][23][24][25][26]. To characterize dynamic variations of glioma cells in the GBM microenvironment without altering genetic and phenotypic properties of the cells, we need to develop adequate tools [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated effective tools to investigate mostly mechanical properties of glioma cells using fluorescence microscopy [15][16][17][18][19][20][21][22][23][24][25][26][27], 2-photon imaging [11,28], atomic force microscopy [16,29,30], single-cell force spectroscopy [16], and microfluidic technologies [31][32][33][34][35][36][37][38][39]. In contrast to mechanical features, electrical properties of glioma cells have not been extensively interrogated.…”
Section: Introductionmentioning
confidence: 99%